Multicultural Education in Elementary Schools: Fostering The Pancasila Student Profile Through an Ethnopedagogical Approach - Muthmainnah, Anti (International Conference on Elementary Education, 2025)
Multicultural education in Indonesia plays a crucial role in shaping the nation's character based on Pancasila. The ethnopedagogy approach emerges as an effective strategy to integrate local and national cultural diversity into the elementary school learning process. This study aims to examine how the ethnopedagogy approach can foster the Pancasila learner profile through multicultural education at the elementary level, as well as strengthen the values of tolerance, justice, and mutual cooperation as part of the nation's character. The method employed includes a literature review and field observations at several elementary schools implementing ethnopedagogy in their teaching. Qualitative analysis was used to assess the influence of this approach on character formation and the application of Pancasila values. The results indicate that ethnopedagogy can enhance students’ awareness of cultural diversity and reinforce attitudes of tolerance, justice, and solidarity. Students better understand and appreciate their own cultural identities while respecting other cultures, thereby contributing to the development of a Pancasila student profile who is faithful and cultured. Multicultural education based on ethnopedagogy is effective in fostering character and Pancasila values among elementary school students. This approach can serve as a vital strategy in cultivating a tolerant generation with strong national identity, capable of living harmoniously within diversity.